Internal Quality Assurance System in Indonesian Basic Education: A Systematic Literature Review - Iffa Afiralda; Maskuri Bakri; Mutiara Sari Dewi; Siti Nur'ain Binti Ahmad Radzuanuddin (Universitas Muhammadiyah Mataram, 2025)
Improving the quality of basic education has become a strategic issue in the global and national development agenda. This study specifically investigates the implementation processes, thematic focus areas, and outcomes of the Internal Quality Assurance System (IQAS) in Indonesian basic education. Employing a qualitative Systematic Literature Review (SLR) methodology, the study synthesizes 45 papers from 2015 to 2025. These articles were were selected using purposive sampling from Google Scholar, DOAJ, SINTA, and Scopus, based on predefined inclusion criteria (articles focused on IQAS in Indonesian basic education) and exclusion criteria (non-empirical papers, non-basic education levels, or unrelated quality systems). Data were collected through document analysis and examined using thematic analysis. The results are: (1) quality certification and accreditation mechanisms, (2) stakeholder participation and school leadership, (3) capacity building and professional development, and (4) integration of digital technologies in quality assurance. Most of the reviewed studies employed qualitative case study approaches. The implementation of IQAS has contributed to strengthening a culture of continuous improvement, enhancing student learning outcomes, and improving equity in access to quality education. These findings imply the need for stronger support for school leadership, greater collaboration in quality management practices, and systematic digital integration into quality assurance processes. The study contributes to the growing literature on education quality assurance and offers practical insights for school administrators and policymakers. Future research should examine implementation challenges in under-resourced or remote areas and evaluate the long-term effectiveness of digital tools in IQAS practices.